Markedsliggørelsens markedsføring - Neoliberale ekspert-, rådgivnings og lobbynetværker - Plehwe, Dieter; Schmelzer, Matthias; Jensen, Jacob (Slagmark - Tidsskrift for idéhistorie, 2020)
This article takes stock of the current literature on neoliberalism and discusses its conceptual benefits, challenges, and avenues for further research. In particular, the article focuses on the transnational network around the Mont Pèlerin Society (MPS) and its activities in marketing the marketization of formerly non-market spheres. Rather than taking for granted pre-existing shared norms, interests, and principled beliefs, this focus helps us understanding the importance of long-term transnational intellectual efforts to develop, shape, prioritize, and generalize specific perspectives and preferences that predated the societal changes associated with the neoliberal ‘counter-revolution’ against planning and the de-commodification of the welfare state. After setting out key advantages of this research agenda, the article provides a rough sketch of the MPS, its structures, evolution, and transnational think tank network. The article ends with a short example of such a transnational network approach in studying the unmaking of the Bretton Woods monetary system.